Penguatan Kapasitas Pengelolaan Radio Komunitas Merapi-Merbabu Community (Mmc-Fm) Melalui Pelatihan Penyusunan Program Siaran Berbasis Mitigasi Bencana Dan Pangan Lokal Di Kawasan Lereng Merapi Desa Samiran Selo Boyolali - Setiawan, Topan; Putro, Fanny Hendro Aryo; Hertini, Etty Sri; Muryanto, Sigit; Chumaeson, Wahyuning; Wicaksana, Aliffia Harsa; Santoso, Bagas (Universitas Pahlawan Tuanku Tambusai, 2024)
The main and urgent focus of the service that will be carried out is an effort to increase the capacity of target partners with training, initiation and AMT (Achievement Motivation Training). The PKM subjects or target partners are given these three treatments, so that the objectives of the PKM activities or programs that have been previously determined will be achieved as well as possible. The focus of the next service is carried out due to the reality in the field of how weak the management aspect is, which is indicated by several facts, namely (1) broadcasts are carried out sporadically adjusting to the